158k views
3 votes
6j-k=20
3k+6j=11
Solve from elimination method

6j-k=20 3k+6j=11 Solve from elimination method-example-1
User Glv
by
8.7k points

1 Answer

0 votes

That's some nice handwriting :)

Eliminate
k and solve for
j.


3 (6j - k) + (3k + 6j) = 3\cdot23 + 11 \\\\ \implies 18j - 3k + 3k + 6j = 69 + 11 \\\\ \implies 24j = 80 \\\\ \implies \boxed{j = (80)/(24) = \frac{10}3}

Now solve for
k.


6j - k = 23 \implies k = 6j - 23 \\\\ \implies k = 6\cdot\frac{10}3 - 23 \\\\ \implies \boxed{k = -3}

User Rick Glimmer
by
8.4k points

Related questions

1 answer
4 votes
169k views
asked Jun 23, 2024 181k views
SvenG asked Jun 23, 2024
by SvenG
8.3k points
1 answer
1 vote
181k views
asked Apr 21, 2024 150k views
ITA asked Apr 21, 2024
by ITA
7.6k points
1 answer
1 vote
150k views